Agricultural tourism development solutions: A case study of Ben Tre province - Nguyen, Thi Thu Hoa; Le , Thi Tu Mi (Journal of Finance - Marketing Research, 2026)
Agricultural tourism is a strategic pillar in Vietnam’s rural development strategy to 2030, particularly for Ben Tre Province, which possesses a unique ecosystem of over 78,000 hectares of coconut plantations. This study aims to systematically assess development conditions and propose comprehensive sustainable solutions to enhance the province’s competitive advantage. Employing a mixed-methods approach, the research utilized primary data from 153 tourists surveyed between February and April 2025 alongside secondary data analysis. were applied to evaluate four key factor groups: resources, facilities, human resources, and local policies. The findings reveal that while Ben Tre has strong resource attractiveness (Mean = 3.79), significant bottlenecks exist in infrastructure specifically 61.4% dissatisfaction with accommodation and human resources, where 68.6% of respondents were dissatisfied with foreign language competency. Notably, international tourists demonstrated significantly higher expectation standards regarding facilities compared to domestic groups (p < 0.001). The paper’s novel contribution lies in addressing the gap between descriptive potential and empirical evaluation a proposed solution framework. This includes synchronized facility upgrades, green management models, and standardized training to advance Ben Tre’s tourism toward global professionalism and sustainability.